Comorbidity between depression, anxiety and obesity and treatment complications (Research, Society and Development, 2021)
Mental disorders such as Major Depressive Disorder and Anxiety Disorders, along with obesity, have grown substantially in the last century. The increase in the consumption of foods rich in fats and sugars and sedentary lifestyle, as well as genetic and everyday factors seem to explain, to some degree, the incidence of metabolic diseases and obesity. Nevertheless, a better understanding of risk factors related to the onset of psychic disorders in certain populations lead to changes in the treatment of these pathologies, favoring comprehensive and multidisciplinary care. Within this scope, the present study aims to analyze whether there is a correlation between depression, anxiety and obesity, when it comes to the multidisciplinary treatment of these pathologies. An integrative bibliographic review was made using articles from the last 10 years (2010-2020) from the databases of Latin American and Caribbean Literature on Health Sciences - LILACS, PubMed, Cochrane and Online Scientific Electronic Library - SciELO, with the descriptors: "Obesity"; "Mental Disorders"; "Anxiety"; "Depression"; "Comorbidities." The literature presents disagreements in the association between obesity, anxiety and depression. Some studies show that there is no statistically significant correlation between BMI, depression and anxietyon. Likewise, other studies show that the correlati between obesity and mood disorders is influenced by the use of psychotropic drugs used in psychiatric treatment, with the potential to influence weight gain. The causal relationships involving depression, anxiety and obesity are still controversial and require more research.